Scheduled Tribes, Reserved Constituencies and Political Reservation in India. Issue 1 (June 2019) - Ambagudia, Jagannath
Abstract: Scheduled Tribes (STs, indigenous people) are one of the most marginalised communities in the political sphere. Political marginalisation of STs due to historical injustices has compelled the Indian state to explore alternative means to ensure adequate representation for them by adopting a political reservation system. Political reservation has, therefore, become their primary means of political empowerment, wherein it has ensured the redistribution of political resources in favour of the marginalised communities. Against this backdrop, the article explores the location of tribal communities in the colonial political system and the reasons for their disproportionate representation, the nature and dynamics of ST reserved constituency and the effects of political reservation on these communities. Further, the article concludes by suggesting that the political reservation system has brought both hope and despair among the STs.